Tertunda Pembagian Harta Waris Kepada Ahli Waris Studi Di Desa Cipatujah - Muhammad Abduh; Roni Nurhidayat (Ahwaluna | Jurnal Hukum Keluarga Islam, 2023)
One of the rituals in Cipatujah Village, Tasikmalaya Regency is the postponement of inheritance distribution. This delay is caused because one of the parents is still alive and the heir is not yet an adult. The purpose of this research is to find out the perspectives of positive law and Islamic law on the postponement of the division of inheritance and its procedures, as well as the perspective of the local government regarding it. This research uses descriptive qualitative methods, including documentation, observation of the application of delayed inheritance distribution, and interviews with community leaders. The juridical-empirical method was also used. The result of this research is that Islamic Law suggests accelerating the process of inheritance distribution if there is no compelling reason. Surah An-Nisa contains this instruction, especially in verses 5, 7, 13, and 14. If all heirs agree unanimously or if there is a shar'i justified reason, the division of inheritance can be postponed. The postponement of the distribution of the inheritance can be justified by the heirs using their legal capacity. Article 830 of the Civil Code and article 175 of the second book of the Compilation of Islamic Law encourage the acceleration of the inheritance distribution process in Indonesia. It is important to remember that postponement of the division of the estate can be authorised if all the heirs agree. As part of the inheritance division process, all outstanding debts, funeral costs, and wills are usually paid before the remaining assets are distributed to the heirs according to their rank of receipt. In Cipatujah Village, there is a custom of delaying the division of inheritance because one parent is still alive and the designated heir is too young to responsibly administer the estate. In Cipatujah Village, the division of inheritance is done independently or with assistance from the authorities or religious and community leaders. In Islamic jurisprudence, under some conditions, such as when there are shar'i justified reasons, the division of inheritance in Cipatujag Village can be postponed. This can happen when one of the parents of the designated heir is still alive and the heir is still a child, in which case the division of inheritance needs to be postponed.